VIDEO PROFIL SMA ADABIAH 2 PADANG - Randa Yuliandri Brian; syafwandi sayafwandi; hendra afriwan (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Adabiah High School is one of the well-known private schools in the city of Padang and one of the national-level private schools. Adabiah 2 Senior High School is very spacious and beautiful with adequate facilities.The making of this video profile aims to create supporting promotional media through Visual Communication Design by showing the aesthetic values of the design on supporting media that can attract consumer interest.The main media in designing this video profile is communication media in the form of audio visual . And supported by various supporting media for school promotions such as calendars, wall of fame, posters, pins, banners, book covers and x-banners.Keywords: Video Profile , audio visual